Delayed Therapy of Descending Aortic Coarctation Results in Anterior Cerebral Rupture: A Case Report - Kele Qin; Jinfu Yang; Mi Tang; Chukwuemeka Daniel Iroegbu; Shijun Hu; Chengming Fan (Frontiers Media S.A., 2021)
Background: Coarctation of the aorta (CoA) is the congenital constriction or narrowing of the aortic lumen. These constrictions are primarily located in the descending aorta causing significant discrepancies in systolic blood pressures of the upper and lower extremities. Thus, a delay in diagnosis and treatment may lead to severe and adverse consequences.Case presentation: Herein, we present a 13-year-old boy with anterior cerebral rupture following a delayed diagnosis for descending CoA. Percutaneous transluminal balloon dilatation and endovascular stent implantation were urgently and successfully performed alongside cerebral clipping of the vascular aneurysm.Conclusion: An early diagnosis is crucial for CoA's successful treatment and management to prevent complications, including anterior cerebral rupture.